(untitled) (Ustozlar uchun, 2026)
For Uzbekistan’s football, the ticket to the 2026 World Cup is not just a sports result. It signifies that the country’s football system, having drawn conclusions from half a century of mistakes, has finally entered an era of "tactical and infrastructural awakening". For many years we dreamed of the status of "Asian Brazilians," but our failures in the international arena were mainly related to gaps in professional preparation and mentality. Today, however, we are witnessing a completely different approach: cold-blooded strategy has replaced emotions.